Pengaruh Kompetensi dan Independensi Auditor Terhadap Kualitas Audit - Lauw Tjun Tjun; Elyzabet Indrawati Marpaung; Santy Setiawan (Jurnal Akuntansi, 2012)
The auditor need both competency and independency to improve the relevance of financial statement. The objective of this research is to know the influence of competency andindependency on the audit quality. The subject of this research are public accountant office at Jakarta Pusat. The result show that the competency has influence on the audit quality and the independency has no influence on the audit quality partially. But the competency and independency have influence on the audit quality simultaneously.